Comparison of periodic face-to-face visits and use of smartphone application during COVID-19 pandemic in clinical follow-up of range of motion in patients with distal humeral fracture - Gholipour, Morteza; Aslani, Hamid Reza; Bonakdar, Sona (Researcher Bulletin of Medical Sciences, 2022)
Objective: As the prevalence of the coronavirus increases, there is now more emphasis on reducing "face-to-face" patient visits. Therefore, the use of smartphones and their special medical applications can play an important role in following up patients. The aim of this study was to evaluate the use of smartphone in evaluating clinical outcomes and range of motion of patients after elbow operation. Materials and Methods: Forty patients were randomly selected from patients undergoing elbow operation. Patients were divided into two groups, so that in the first group, the patients were visited and then were followed-up for 2,6, and 12 weeks as well as 6 months after first visit by smartphone connection and delivering the pictures and videos of involved organ to the physician as well as having the physical examination him. In the second group, all assessments were performed by clinical visiting at the same time points. Results: The two groups were similar in baseline characteristics including demographics; the side of involved elbow, type of fracture, surgical approach, operation time, and mean Mepi score. Assessing the postoperative complications and also patients' satisfaction was also similar in both groups. There was no difference in different range of elbow motion degrees between the case and control groups at different times of following-up as well as the progress in motion of elbow after surgery in two groups. Moreover, there was no significant difference between the range of motion evaluated by smartphone and physical examination. Conclusion: The use of the smartphone has a high degree of accuracy and sensitivity in assessing the status of elbow range of motion after surgical treatment, both in the short and long term after surgery.